2018
DOI: 10.1037/xhp0000459
|View full text |Cite
|
Sign up to set email alerts
|

Smile! Social reward drives attention.

Abstract: Human social behavior is fine-tuned by interactions between individuals and their environments. Here we show that social motivation plays an important role in this process. Using a novel manipulation of social reward that included elements of real-life social exchanges, we demonstrate the emergence of attentional orienting for coincidental spatial associations that received positive social reward. After an interaction with the experimenter, participants completed a computerized task in which they received posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…We used a type of secondary reward, i.e., monetary compensation, in the current study. It should be noted that other forms of reward, including endogenous rewards associated with the primary task (Xue et al, 2015 ), primary rewards, such as water (Seitz et al, 2009 ) and juice (Imai, Kim, Sasaki, & Watanabe, 2014 ), and social reward (Hayward, Pereira, Otto, & Ristic, 2018 ), have also been found to be effective in initiating and/or improving perceptual learning. Whether there is a single mechanism for the different forms of reward or there are multiple reinforcement processes that differentially modulate visual perceptual learning remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…We used a type of secondary reward, i.e., monetary compensation, in the current study. It should be noted that other forms of reward, including endogenous rewards associated with the primary task (Xue et al, 2015 ), primary rewards, such as water (Seitz et al, 2009 ) and juice (Imai, Kim, Sasaki, & Watanabe, 2014 ), and social reward (Hayward, Pereira, Otto, & Ristic, 2018 ), have also been found to be effective in initiating and/or improving perceptual learning. Whether there is a single mechanism for the different forms of reward or there are multiple reinforcement processes that differentially modulate visual perceptual learning remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Another area of investigation that indicates a dynamic relationship between perceptual and interpretive processes relates to the effects of the emotional context, with evidence suggesting that interpretive operations, such as the detection of the emotionally consistent and contextually appropriate facial expressions, act to boost the power of emotionally arousing stimuli, like those signaling threat, in attracting attention . Additional evidence shows that perceptual analyses are also affected by socio‐evaluative operations, whereby initially neutral visual stimuli become perceived as conveying socially relevant information after they have been imbued with social reward …”
Section: The Relationship Between the Three Core Processesmentioning
confidence: 99%
“…Such incidental learning of others’ social reliability and prosociality modulates the strength of gaze following, with greater responses elicited by gaze cues of reliable, relative to unreliable, faces, especially in high socially‐competent observers (see also, Ref. ). Thus, social affiliation also affects social attention and, along with social status, represents another dimension that supports the dynamic prioritization of social information based on agents’ identity and their social characteristics.…”
Section: The Three Core Processesmentioning
confidence: 99%
“…We conducted a power analysis to determine the required sample size by including studies that have shown masked free-choice priming effects (Schlaghecken and Eimer, 2004;Kiesel et al, 2006;Ocampo, 2015). Cohen's standardized difference scores (d z ) were estimated using the reported paired-sample t-test values and sample sizes (i.e., d z = t/ √ N; Cohen, 1988;Rosenthal, 1991;Hayward et al, 2018). The calculations were based on results reflecting differences between proportion of congruent and incongruent choices on free-choice priming trials since our main variable of interest was the choice proportion.…”
Section: Participantsmentioning
confidence: 99%